The economic impacts of the foreign direct investments: panel estimation by sectors on the case of Macedonian economy - Aneta Krstevska; Magdalena Petrovska (National Bank of the Republic of Macedonia, 2011)
This paper elaborates the economic impacts of the foreign direct investments (FDI) on the case of Macedonian economy. Most developing countries consider FDI a vital source for their development. Anyway, it is quite difficult to measure the economic effects of FDI over the host country, having in mind their numerous direct and indirect effects. Besides the amount of FDI inflows, the economic benefit will also depend on their structure. Based on a panel regression technique, the FDI impacts on GDP, export and employment on the case of Macedonian economy have been estimated, taking into account for their structural dimension. The main conclusion of the analysis is that the FDI inflows were important factor for GDP growth and export performances of the Macedonian economy. On the other hand, the FDI impact over employment is negative mainly due to the low level of green field investments and non attractiveness of the labor intensive industry for the foreign investors. These findings regarding the type and sector distribution of the FDI inflows are very important for the policy makers and imply a need for a strategic approach in this field.
Keywords: E22; E24; C23; 330; foreign direct investments; tradable sector; non tradable sector; economic growth; export; employment